Violence against women and girls research: Leveraging gains across disciplines - Kathryn Falb; Amber Peterman; Ragnhild Nordås; Anjalie Field; Roni Porat; Lindsay Stark (Proceedings of the National Academy of Sciences, 2025)
Violence against women and girls (VAWG) is a leading cause of mortality and morbidity worldwide, linked to numerous health, economic, and human rights outcomes. Target 5.2 of the Sustainable Development Goals calls for elimination of all forms of VAWG; however, progress toward achieving this goal has been inadequate. A lack of sufficient data and evidence has hindered global efforts to meet this target and hold governments accountable for action. While there have been substantial advancements in VAWG research methodology over the past three decades, researchers from diverse disciplines tend to work in silos, inhibiting progress in VAWG research. To address this challenge, we offer four key recommendations to support researchers in expanding transdisciplinary approaches: 1) leverage insights from a variety of VAWG data sources, 2) improve precision of VAWG definitions and outcomes, 3) create strategies to address underreporting, and 4) advance research ethics and equity. We conclude with a call to action for researchers, institutions, and donors to advance transdisciplinary research and foster collaboration, learning, and cross-fertilization across scientific fields to accelerate VAWG prevention efforts now and for future generations.